1993
DOI: 10.1111/j.1550-7408.1993.tb04913.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Quantitative Protargol Stain and Lugol's and Bouin's Fixatives On Cell Size: A More Accurate Estimate of Ciliate Species Biomass

Abstract: ABSTRACT. The quantitative protargol stain (QPS) is used to estimate ciliate biomass and species composition from mixed field samples. Length, width, breadth and volume of live Euplotes sp., Eutintinnus sp., Strobilidium spiralis, Strombidium acutum, and Gymnodinium sanguineum were compared with 0.6% acid Lugol's fixed, 5% Bouin's fixed, and QPS cells. Cells shrank due to treatments (ANOVA and Tukey's test, α= 0.05). Protistan post‐fixation cell volume (as a percentage of live volume) was 55%‐80% for acid Lugo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 19 publications
2
68
1
Order By: Relevance
“…Obvious shrinkage of stained ciliates was noticeable after silver preparation. Therefore, the calculated cell volumes were multiplied with a correcting factor of 0.4 (Jerome et al, 1993). In the case of Crustacea (Cladocera and Copepoda), double samples of the volume 0.5 dm 3 were collected and pooled to reduce heterogeneity in crustacean distribution and sampling variability, thus the final volume of a sample measured 1 dm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Obvious shrinkage of stained ciliates was noticeable after silver preparation. Therefore, the calculated cell volumes were multiplied with a correcting factor of 0.4 (Jerome et al, 1993). In the case of Crustacea (Cladocera and Copepoda), double samples of the volume 0.5 dm 3 were collected and pooled to reduce heterogeneity in crustacean distribution and sampling variability, thus the final volume of a sample measured 1 dm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Ciliates are highly perishable, and their motility is a species-specific feature, so species determination and measurements were carried out on live material immediately on return to the laboratory, following silver impregnation (Augustin et al 1984). The stained ciliates had suffered obvious shrinkage following the impregnation, so calculated cell volumes were multiplied by a correcting factor of 0.4 (Jerome et al 1993). Taxonomic identification was primarily based on the key in Foissner & Berger (1996).…”
Section: Methodsmentioning
confidence: 99%
“…This has also been demonstrated in previous studies for ciliates (Putt and Stoecker 1989, Ohman and Snyder 1991, Jerome et al 1993, Stoecker et al 1994, flagellates (Borsheim and Bratbak 1987, Choi and Stoecker 1989, Menden-Deuer et al 2001, several phytoplankton groups Fig. 1.…”
Section: Discussionmentioning
confidence: 48%
“…(Verity et al 1992, Montagnes et al 1994, and cyanobacteria (Hawkins et al 2005), with an average protozoan volume reduction of 33% to 40%. Maximum shrinkage rates are published, with a 40% volume reduction for cyanobacteria (Hawkins et al 2005), 57% for naked heterotrophic flagellates (Borsheim and Bratbak 1987), and 45% for ciliates (Jerome et al 1993). Studies of seven different phytoplankton groups showed a mean length reduction by 10.7% (ranging from 3.1% to 22.2%), including three Bacillariophyceae species (mean size reduction 7.1%) (Montagnes et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation